Equity Financing and Firm Value; Short Run and Long Run Dynamics: A Generalized Method of Moments Approach - Oganda, Aloys (International Journal of Economics, 2023)
The Kenyan manufacturing sector's contribution to the economy has been declining. It has stagnated at 10% of the gross domestic product (GDP), contributing to an average of 10% from 1964-1973 and marginally increased to 13.6% from 1990-2007 and has been below 10% in recent years further dropping to 8.4% in 2017 and 7.1% in 2020 ultimately hitting its lowest in 2022 of 7.2%. The government has renewed its efforts to revive the sector to grow its contribution to GDP to 20% by 2030. Financing by equity is significant for listed firms. This study applied Dynamic Unbalanced Panel analysis techniques using Secondary data for 10-year period (2010 - 2019) with the study population comprising of 9 listed firms. A census of the firms was done and resulted to 86 observations. Focus was on equity financing moderated by economic growth and earnings volatility on firm value which was proxied by Tobin's Q and EVA. Pecking order guided the study. Longitudinal research design was used as it is appropriate when dealing with panel data. STATA version 15 was used for analysis. Model estimation followed a two Step System GMM testing the study hypotheses at 5 % significance level. Pearson correlation coefficient was used to show the strength and direction of association among the study variables. Equity financing had a negative correlation with Tobin Q (r = -0.2682). The regression weight being (Î²= -0.1674526; p = 0.002 < 0.005). On the other hand, Equity to assets ratio (EAR) was found to have positive correlation with Ln EVA (r= 0.5218). The regression coefficient was positive but not significant (Î² = 0.2901601; p = 0.087 > 0.05) and hence concluding that it improved firm value marginally. The study therefore concluded that equity financing structure directly determines value of the firm by eroding Tobin Q and hence equity financing need to be limited. Future studies can consider static panel analysis models and other panel data econometric techniques. Purpose: The purpose of the study was to analyze the relationship between equity financing and the value of the firm. Methodology: The study adopted a longitudinal research design. The target population comprised the nine manufacturing firms which were listed on the Nairobi Securities exchange (NSE) for the period 2010 to 2019. The study used secondary data from the published financial statements of the firms. A census of the 9 manufacturing firms was done and this comprised a total of 86 observations due to missing data during the study period hence the Unbalanced Panel Analysis approach. Model Selection followed Arellano &Bond (1991) Panel data procedures. A two-step system GMM was used. STATA Version 15 software was used for data analysis. Unit root tests were conducted using the Im-Pesaran-Shin and Fisher-type tests which allow for unbalanced panels. Findings: It was found that equity financing as was proxied by equity to assets ratio (EAR) had a weak negative correlation with Tobin Q. The regression weight for EAR with Tobin Q was negative and significant. The null hypothesis was thus rejected. On the other hand, EAR was found to have a moderate positive correlation with Ln EVA The regression coefficient was positive but not significant hence, the null hypothesis was not rejected. This objective showed mixed results possibly due to the different performance proxies. Unique Contribution to Theory, Practice and Policy: The finding supports the Myers & Majluf model (1984) which posits that outside investors rationally discount the firm's stock price when managers issue equity instead of riskless debt. To avoid this discount, managers should avoid equity whenever possible. It also supports the Pecking Order theory that equity financing should be used as the last option. To the practice, corporate finance managers need to minimize use of equity financing due to its negative effect on firm value. For policy, The National Treasury needs to formulate an incentive driven policy targeting the manufacturing sector due to its critical role in Economic development as can be seen from the industrialized economies.